2003
DOI: 10.1021/bp025604g
|View full text |Cite
|
Sign up to set email alerts
|

Small Increases in pH Enhance Retroviral Vector Transduction Efficiency of NIH‐3T3 Cells

Abstract: Increases in pH between 7.1 and 7.7 increase the efficiency of polybrene (Pb)- and protamine sulfate (PS)-aided retroviral transduction of NIH-3T3 cells in a serum-lot-dependent manner. The increase in Pb-aided transduction efficiency at pH 7.7, relative to the value at pH 7.33, ranged from 13% to 49% for three serum lots. For a constant Moloney murine leukemia virus (MMLV) vector dilution at pH 7.33, three different serum lots resulted in absolute transduction efficiencies ranging from 29% to 53% using Pb. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
3
6
1
Order By: Relevance
“…/hgtb.2013 In summary, we have shown that there can be significant variability between different FBS production lots in the production of viral vectors. Our data are consistent with prior studies with lentiviral vectors (Denning et al, 2013) as well as MMLV and MSCV vectors ( Jensen et al, 2003). Our data also indicate that when serum will be used for the production of more than one type of retroviral vector, it is prudent to test the production of all vectors.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…/hgtb.2013 In summary, we have shown that there can be significant variability between different FBS production lots in the production of viral vectors. Our data are consistent with prior studies with lentiviral vectors (Denning et al, 2013) as well as MMLV and MSCV vectors ( Jensen et al, 2003). Our data also indicate that when serum will be used for the production of more than one type of retroviral vector, it is prudent to test the production of all vectors.…”
Section: Resultssupporting
confidence: 92%
“…Although there has been a movement toward serum-free medium for the production of viral vectors (Falkner et al, 2006), FBS is still commonly used for the production of preclinical and clinical viral vector preparations (DiGiusto et al, 2010). The importance of macromolecules, specifically lipids such as cholesterol, to obtain high-quality vector preparations has been described for the production of MLV vectors (Rodrigues et al, 2009) and pH may also play a role ( Jensen et al, 2003). The presence of antiviral antibodies such as bovine foamy virus (BFV) antibodies may have also affected the resulting foamy viral titers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as specified in the protocol of the manufacturer of pLenti vectors (Invitrogen), polybrene may be toxic to primary cell cultures such as primary neurons and therefore should be carefully titrated [29]. Since a previously published study suggested that small variances in the pH of transduction media may significantly influence transduction efficiency [16], transduction culture mediums with pH ranging from 7.0 to 7.6 were tested. Optimal transduction of DEAE-dextran-containing cultures typically occurred at pH 7.0 – 7.2 (Figure 2D); however, the effect of pH appeared to be minor.…”
Section: Resultsmentioning
confidence: 99%
“…However, several recent studies have demonstrated that the initial step of virus binding does not involve specific envelope-receptor interactions but rather receptor-independent binding events [14, 15]. The efficiency of this initial event and, consequently, lentiviral transduction is diminished by strong electrostatic repulsion between the negatively charged cell and an approaching enveloped virus [16, 17]. Methods designed to overcome this problem include centrifugation of targets cells with virus at low speeds, co-localization of cells and virus on immobilized proteins, and employing multiple rounds of transduction [17, 18].…”
Section: Introductionmentioning
confidence: 99%